Gender, diabetes education, and psychosocial factors are associated with persistent poor glycemic control in patients with type 2 diabetes in the Joint Asia Diabetes Evaluation (JADE) program. (9th April 2015) - Yin, Junmei; Yeung, Roseanne; Luk, Andrea; Tutino, Greg; Zhang, Yuying; Kong, Alice; Chung, Harriet; Wong, Rebecca; Ozaki, Risa; Ma, Ronald; Tsang, Chiu‐Chi; Tong, Peter; et al.
Abstract: Background: Factors associated with persistent poor glycemic control were explored in patients with type 2 diabetes under the Joint Asia Diabetes Evaluation (JADE) program. Methods: Chinese adults enrolled in JADE with HbA1c ≥8% at initial comprehensive assessment (CA1) and repeat assessment were analyzed. The improved group was defined as those with a ≥1% absolute reduction in HbA1c, and the unimproved group was those with <1% reduction at the repeat CA (CA2). Results: Of 4458 enrolled patients with HbA1c ≥8% at baseline, 1450 underwent repeat CA. After a median interval of 1.7 years (interquartile range[IQR] 1.1−2.2) between CA1 and CA2, the unimproved group ( n  = 677) had a mean 0.4% (95% confidence interval [CI] 0.3%, 0.5%) increase in HbA1c compared with a mean 2.8% reduction (95% CI −2.9, −2.6%) in the improved group ( n  = 773). The unimproved group had a female preponderance with lower education level, and was more likely to be insulin treated. Patients in the improved group received more diabetes education between CAs with improved self‐care behaviors, whereas the unimproved group had worsening of health‐related quality of life at CA2. Apart from female gender, long disease duration, low educational level, obesity, retinopathy, history of hypoglycemia, and insulin use, lack of education from diabetes nurses between CAs had the strongest association for persistent poor glycemic control. Conclusions: These results highlight the multidimensional nature of glycemic control, and the importance of diabetes education and optimizing diabetes care by considering psychosocial factors.